Systematic Literature Review on Crack Measurement in Concrete Silos - Oliveira, Diogo Cavalcanti; Lordsleem Jr, Alberto Casado; Cordeiro, Laura Nogueira; Costa, Thais Cohen de Almeida; Amorim, Emanoel Silva de; Póvoas, Yêda Vieira (National Journal of City Management, 2025)
This research presents a Systematic Literature Review (SLR) on the main methods for crack identification in concrete structures, focusing on their applications in silos, as well as their advantages and disadvantages. The aim of this article is to conduct a critical analysis of the most relevant scientific publications on crack measurement in concrete structures, emphasizing the comparison of different methods. Throughout this study, the characteristics and pathological manifestations of concrete silos are discussed, along with traditional and advanced methods for crack identification. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, articles published between 2016 and 2023 were selected from the Web of Science, Science Direct, SCOPUS, and Engineering Village databases. The results highlight a growing trend in the use of technologies such as UAVs, Laser Scanning, and emerging techniques like machine learning and deep learning. These technologies are seen as promising for improving the accuracy and efficiency of early structural damage detection, with significant practical implications for industrial and civil construction sectors. The contribution of this study lies in the analysis of market trends, providing a critical perspective on existing technologies that propose solutions to the challenges faced in concrete infrastructure inspection.